Maternal age and parity associated with low birth weight infants - Afifah, Intan; Ariningtyas, Ninuk Dwi; Djalilah, Gina Noor; Anas, Muhammad (Gaceta Médica de Caracas, 2021)
Introduction: Low birth weight (LBW) infants indicate infant morbidity and infant mortality rates. In Indonesia, the infant mortality rate is still very high, with 32 deaths per 1 000 live births. The purpose of this study is to prove a relationship between maternal age and parity with LBW infants.